2014
DOI: 10.1021/la501511s
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Non-Brownian Particle-Based Crystals

Abstract: Particle-based crystals have been explored in the literature for applications in molecular electronics, photonics, sensors, and drug delivery. However, much of the research on these crystals has been focused on particles of nano- and submicrometer dimensions (so-called colloidal crystals) with limited attention directed toward building blocks with dimensions ranging from tens to hundreds of micrometers. This can be attributed, in part, to the fact that the underlying thermal effects in these larger systems typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Angewandte microparticle-based structures can be created with new opportunities for varying macroscopic hierarchy,s urface functionalization, and the diffusive properties.E ngineering these aforementioned properties allows the design of novel materials for applications for which nanoscale features are not suitable.H erein we explore an ew method of creating autonomously assembled, microparticle-based crystals from particles with varying dimensions and compositions.S pecifically,w ee mploy sonication as am eans of artificially thermally treating as ystem of large,n on-Brownian microparticles such that we induce organization among particles up to 0.1 mm in size. [11] Furthermore,w eo bserve that it is possible to produce av ariety of predictable stoichiometric patterns (corresponding to N S/L )from particles that are two to three orders of magnitude larger than those previously studied. We have achieved particle organization for mixtures containing particles as small as d S = 0.6 mma nd as large as d S = 21 mmc ombined with d L = 100 mm, where d is particle diameter, and Sa nd Lr epresent the small and large particle populations,respectively.Byfurther increasing the g S/L above 0.21, we have formed crystals among particles where d S = 21 mma nd d L = 75 mm, yielding ar atio of g S/L = 0.28.…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…Angewandte microparticle-based structures can be created with new opportunities for varying macroscopic hierarchy,s urface functionalization, and the diffusive properties.E ngineering these aforementioned properties allows the design of novel materials for applications for which nanoscale features are not suitable.H erein we explore an ew method of creating autonomously assembled, microparticle-based crystals from particles with varying dimensions and compositions.S pecifically,w ee mploy sonication as am eans of artificially thermally treating as ystem of large,n on-Brownian microparticles such that we induce organization among particles up to 0.1 mm in size. [11] Furthermore,w eo bserve that it is possible to produce av ariety of predictable stoichiometric patterns (corresponding to N S/L )from particles that are two to three orders of magnitude larger than those previously studied. We have achieved particle organization for mixtures containing particles as small as d S = 0.6 mma nd as large as d S = 21 mmc ombined with d L = 100 mm, where d is particle diameter, and Sa nd Lr epresent the small and large particle populations,respectively.Byfurther increasing the g S/L above 0.21, we have formed crystals among particles where d S = 21 mma nd d L = 75 mm, yielding ar atio of g S/L = 0.28.…”
mentioning
confidence: 89%
“…[10] Recently,weshowed that one can bridge this gap in materials fabrication by using ultrasonic agitation to mimic Brownian motion (or granular vibration), and induce spontaneous assembly of microspheres with dimensions ranging from the nano-to the milliscales into hexagonal close-packed (HCP) two-and three-dimensional crystals. [11] Herein, we extend this bottom-up assembly approach to mixed systems of particles that include as pan in length scale that is larger than any explored to date to attain complex hierarchical crystalline formations from binary and multicomponent particle mixtures.B yd oing so,w eh ave created stoichiometric configurations of large,non-Brownian particles that resemble those formed naturally by atoms and molecules and heretofore have been reported only for nanoparticles. [12][13][14] Specifically,w ee xamine ar ange of radii ratios (g S/L )a nd number ratios (N S/L )o fs mall (S) and large (L) microparticles within amixture to explore awide range of resulting microstructures.Additionally,through post-processing of these microstructures,w eh ave demonstrated that it is possible to evolve these ordered arrays into binary,i nverted crystalline structures with customizable hierarchically ordered features and pore configurations that mimic those in naturally occurring porous materials (such as zeolites).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Also on centimetrescales, magnetic forces have been used to form particles rather than structures, such as the spontaneously folding elastomeric sheets with embedded electronics; as demonstrated by Boncheva et al (2005). Lash et al (2015) showed that polystyrene beads self-assemble into HCP packed structures by solvent evaporation. Larger polystyrene particles (>18 µm) required additional disturbing energy (ultrasonic energy) as a disturbing energy source to self-assemble.…”
mentioning
confidence: 99%